863 Cancer incidence among tanker crews in a cohort study of swedish seafarers. (24th April 2018) - Andersson, E; Forsell, K; Björ, O; Nilsson, R
Abstract : Introduction: Increased rates of leukaemia have been found among tanker crews. Exposure to benzene could be a cause since many products transported on tankers contain benzene. In a cohort of seafarers we studied cancer incidence among tanker crews. Methods: All persons in the Swedish Registry of Seafarers 1985–2011 with registered work periods were included in the total cohort (n=75 745) and followed up for cancer incidence from 1985 or first work period to emigration, cancer or 2011. A sub-cohort of tanker crews (n=14 596 with at least one month on tankers) were used for this study. Standardised incidence ratio (SIR) were analysed with 95% confidence intervals (CI) in relation to the Swedish population. Result: Total cancer risk for tanker crews was SIR 1.07 (cases n=1006, 95% CI: 1.01 to 1.14). The risk for lung cancer and leukaemia was increased, SIR 1.86 (n=127, 95% CI: 1.54 to 2.19) and SIR 1.40 (n=43, 95% CI: 1.01 to 1.82), respectively. The risk for lymphoma and multiple myeloma was not increased. Most (90%) of the crew members were men. There was a trend to normalised cancer incidence with time, analysing first employment before 1985, 1985 to 1991 and after 1991, significant for lung cancer (p=0.03). In the total cohort the risk for lung cancer was SIR 1.52 (95% 1.37–1.66) and for leukaemia SIR 0.94 (95% 0.78–1.11). Discussion: Seafarers working on tankers had an increased risk for leukaemia, which other seafarers did not have. Measurements on product tankers have shown that the deck crew could be exposed to rather high concentrations of benzene, especially during loading, unloading and tank cleaning operations. During the last decades, benzene exposure on tankers has presumably decreased (lower benzene content in gasoline, modern shipping with closed loading and unloading of tankers), possibly also resulting in decreased leukaemia incidence.